Reoperation-free survival in patients subjected to endovascular treatment of diseases of the aorta (2019)
Introduction: The endovascular management for diseases of the aorta has increased as an option for patients of high risk for conventional open surgery. The short-term mortality, disease-free and reoperation results, show favourable outcomes compared to open surgery, but there are no results available in this country for the medium (1-12 months) and long-term (>1 year). Methods: A bi-directional cohort study, in which the retrospective segment was conducted on patients subjected to endovascular management with an aortic replacement, and the prospective segment on the follow-up of the patients. Results: A total of 194 patients, subjected to endovascular treatment and met the inclusion criteria, were identified between April 2002 and December 2015. The follow-up was completed in 82.2% of cases. There were 92 (56.8%) cases of abdominal aorta with a mean follow-up of 4.9 years (95% range; 2.5-8.9). The calculated survival was 92% at one year, 86% at 2 years, and 66.4% at 5 years. The period free of disease was 88.7% at one year, 86.4% at 2 years, and 78.5% at 10 years, with 13 patients requiring re-operation. There were 67 cases of thoracic aorta, with a mean follow-up of 5.3 years (95% range; 2.9-10.2). The calculated survival was 94% at one year, 90.7% at 2 years, and 75.2% at 5 years. The period free of disease was 88.7% at one year, 86.4% at 2 years, and 78.5% at 10 years, and 9 patients required re-operation. Conclusions: The results obtained are favourable and are encouraging to continue offering the endovascular approach since the re-operation survival is similar to that reported in the literature. © 2018 Sociedad Colombiana de Cardiología y Cirugía Cardiovascular